Coping with religious tolerance and gender equality: comparing Islam and good governance perspectives - Ridho Al-Hamdi (IAIN Salatiga, 2015)
Using literature review and in-depth analysis, the study is going to examinethe comparative perspective between Islam and the West in addressing twomain public issues, i.e. religious tolerance and gender equality. More specifi-cally, this study will provide the policy, agenda and strategy of Islam and goodgovernance in coping with those two issues. Therefore, the finding of thestudy is that Islam and good governance precisely have no distinctive concept,policies, agendas and strategy. In contrast, both of them obviously agree thatreligious tolerance and gender equality is important for human lifesustainability. The result, Muslim communities have to disseminate the no-tion of the compatibility between Islam and good governance to the world.Menggunakan review literatur dan analisis mendalam, penelitian ini akanmenguji perspektif komparatif antara Islam dan Barat dalam menjawab duamasalah umum utama , yaitu toleransi beragama dan kesetaraan gender . Lebihkhusus, penelitian ini akan menyoroti kebijakan, agenda dan strategi Islamdan pemerintahan yang baik dalam menjawab dua masalah di atas. Temuan studi ini adalah bahwa Islam dan pemerintahan yang baik justru tidak memilikikonsep yang khas, kebijakan, agenda dan strategi. Sebaliknya, keduanya jelasmenyepakati bahwa toleransi beragama dan kesetaraan gender penting untukkeberlanjutan kehidupan manusia. Hasilnya, masyarakat Muslim harusmenyebarluaskan gagasan kompatibilitas antara Islam dan pemerintahan yangbaik kepada dunia.